2014
DOI: 10.1021/nl503584q
|View full text |Cite
|
Sign up to set email alerts
|

Gold–Copper Nano-Alloy, “Tumbaga”, in the Era of Nano: Phase Diagram and Segregation

Abstract: Gold–copper (Au–Cu) phases were employed already by pre-Columbian civilizations, essentially in decorative arts, whereas nowadays, they emerge in nanotechnology as an important catalyst. The knowledge of the phase diagram is critical to understanding the performance of a material. However, experimental determination of nanophase diagrams is rare because calorimetry remains quite challenging at the nanoscale; theoretical investigations, therefore, are welcomed. Using nanothermodynamics, this paper presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 61 publications
9
119
1
2
Order By: Relevance
“…Shortly after reports identified copper as an antibacterial reagent, 92 synthesis techniques for producing nanosized copper were developed. 93 It has been reported that the antibacterial characteristics displayed by copper are a result of cellular damage after contact between released Cu 2+ ions and bacteria membrane. This section analyzes different synthesis, antibacterial properties of the structure nanoparticle, comparison of different shapes and sizes, promising composites, and toxicity properties of copper nanomaterial.…”
Section: Copper Nanomaterialsmentioning
confidence: 99%
“…Shortly after reports identified copper as an antibacterial reagent, 92 synthesis techniques for producing nanosized copper were developed. 93 It has been reported that the antibacterial characteristics displayed by copper are a result of cellular damage after contact between released Cu 2+ ions and bacteria membrane. This section analyzes different synthesis, antibacterial properties of the structure nanoparticle, comparison of different shapes and sizes, promising composites, and toxicity properties of copper nanomaterial.…”
Section: Copper Nanomaterialsmentioning
confidence: 99%
“…From the catalytic point of view, supported copper and supported gold nanoparticles are very active for oxidation reaction and Cu/Au nanoparticulates have been reported to be catalytically active for a variety of reactions, in particular for the oxidation of CO and of alcohols to produce biofuels [70][71][72]. Moreover, supported gold catalytic systems can also operate as highly selective catalysts for the hydrogenation of important feedstocks such as benzaldehyde [73] and nitrobenzene [74].…”
Section: B Reactivitymentioning
confidence: 99%
“…A nano-phase diagram of structure versus temperature has been developed for gold and silver from experiments and density functional theory (DFT) [11,12]. A phase diagram for copper has been produced as an alloy with gold for nanoclusters [13]. We model all three noble metals, gold, silver, and copper and use gold to present typical data, with tabular data compiled for silver and copper.…”
Section: Introductionmentioning
confidence: 99%